Pemberdayaan Kelompok Bungong Chirih melalui Produksi Tenun Lidi Nipah - Adi Bejo Suwardi; Baihaqi Baihaqi; Zidni Ilman Navia; Syardiansah Syardiansah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Bungong Chirih group is one of the handicraft women groups in Aceh Timur District which has produced various kinds of handicrafts. The lack of equipment technology facilities and limited member's knowledge were crucial problems in producing high-quality handicraft products. The aim of this activity is to produce high-quality nipah stick weaving products. The activity was carried out for five months from April to August 2019. These activities involved 22 participants of Bungong Chirih members group. The mixed methods to develop group capacities in producing quality products were carried out including. group discussions coordination, socialization, training and mentoring. The results of group assessment after the program show that knowledge of the group members on producing various kinds of nipah stick weaving has increased. Twenty group members (90.9%) have an excellent understanding of the whole of training materials; two members (9.1%) have a moderate understanding of the training material. The 81.8% group members that participating in the training are very satisfied with the program and 18.2% are just satisfied. From the mentoring programBungong Chirih women groups are able to produce 25 units of tissue boxes, 15 units of napkins, 2 units of beverage packaging boxes, 8 units of maps, 6 pairs of hotel slippers, 8 units of female bags and 3 units of flower vases. Bungong Chirih women groups are able to develop a business plan that has been cascaded into the group annual work program.